2016
DOI: 10.1111/jocn.13284
|View full text |Cite
|
Sign up to set email alerts
|

A structured framework improves clinical patient assessment and nontechnical skills of early career emergency nurses: a pre–post study using full immersion simulation

Abstract: HIRAID should be considered for integration into clinical practice to provide nurses with a systematic approach to patient assessment and potentially improve the delivery of safe patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…The areas evaluated by our assessment tool were in keeping with areas previously identified as core skills for nursing staff (Carroll, 2004, Resuscitation Council, 2016, Munroe et al, 2016, adding validity to our assessment instrument, and both the format of the course and the areas of assessment were comparable to more recently published work looking at the effect of simulation training for medical students (Hogg & Miller, 2016), again adding validity to the methodology and results of this work.…”
Section: Summary Of Findingssupporting
confidence: 69%
See 1 more Smart Citation
“…The areas evaluated by our assessment tool were in keeping with areas previously identified as core skills for nursing staff (Carroll, 2004, Resuscitation Council, 2016, Munroe et al, 2016, adding validity to our assessment instrument, and both the format of the course and the areas of assessment were comparable to more recently published work looking at the effect of simulation training for medical students (Hogg & Miller, 2016), again adding validity to the methodology and results of this work.…”
Section: Summary Of Findingssupporting
confidence: 69%
“…The areas evaluated for subject confidence were selected based on a recent study that identified several essential skills for nurses working in the emergency setting (Munroe et al, 2016), specifically; history taking, assessment and identification of red flags, interventions, diagnostics, reassessment and communication. These areas were also identified in a meta-analysis as some of the core skills for nurses working in the acute setting (Carroll, 2004) adding validity to the assessment tool.…”
Section: Course Evaluationmentioning
confidence: 99%
“…The application of the KTA Cycle in the present study is illustrated in Figure . The Knowledge Creation phase represents the development and testing of the HIRAID assessment framework in the simulated setting as previously reported (Munroe, Buckley et al., ; Munroe, Curtis et al., ). The Action Cycle displays how the HIRAID education workshop was devised to test the effects of the HIRAID assessment framework in the simulated setting and the methods used in this study to identify facilitators and barriers and select additional and/or alternate interventions to optimise future implementation of the framework into emergency nursing practice.…”
Section: Methodsmentioning
confidence: 99%
“…Following ethics approval from the relevant Human Research and Ethics Committee (HREC approval: LNR/13/WMEAD/44), in December 2013 emergency nurses were invited to participate in the study through an expression of interest placed in six New South Wales (NSW) Hospital EDs in Australia. Sample size and participant inclusion criteria were determined by outcomes measured in the studies conducted parallel to this mixed methods study with a primary quantitative drive (Munroe, Buckley et al., ; Munroe, Curtis et al., ). As the HIRAID assessment framework was originally devised to provide new nurses to the ED with a structured approach to patient assessment, Registered Nurses with <3 years post‐registration experience currently working in an emergency department were selected to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation